2022
DOI: 10.17645/pag.v10i1.4758
|View full text |Cite
|
Sign up to set email alerts
|

All About Feelings? Emotional Appeals as Drivers of User Engagement With Facebook Posts

Abstract: Political campaigns routinely appeal to citizens’ emotions, and there is evidence that such appeals influence political behaviour. Social media, an important arena through which political actors communicate with voters, provide a rich source of data for investigating not only which communication strategies they use but also which of these engage followers. Building on political psychology and political communication literature, the present study investigates the relationship between appeals to specific emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Findings are in keeping with literature linking the expression of anger with challenges to autonomy ( 20 ) and support a relationship between appeals for anger and engagement with online posts ( 22 ). Posts expressing anger, sometimes through the use of metaphors and idioms, often elicited empathetic responses in which people shared their problems or experiences to acknowledge confusion or concern.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Findings are in keeping with literature linking the expression of anger with challenges to autonomy ( 20 ) and support a relationship between appeals for anger and engagement with online posts ( 22 ). Posts expressing anger, sometimes through the use of metaphors and idioms, often elicited empathetic responses in which people shared their problems or experiences to acknowledge confusion or concern.…”
Section: Discussionsupporting
confidence: 85%
“…A linguistic inquiry and word count study investigating open-ended diary responses found that anger expressions were more related to daily experienced anger than expressions of anxiety, sadness, depression, and positive emotion and their corresponding daily affect ( 21 ). In some cases, anger has been described as a strong driver of political participation and appeals to anger have been found to strongly predict engagement with Facebook posts ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“… Bil-Jaruzelska and Monzer (2022) examined the relationship between emotions and user engagement with political Facebook posts during the Brexit referendum, and found that engagement with a post substantially increased when appealing to anger, enthusiasm, and pride. A relationship between appeals to specific emotions (i.e., fear, anger, enthusiasm, and pride) and the engagement of users was observed.…”
Section: Discussionmentioning
confidence: 99%
“…There is infrequent reliance on a defined taxonomy to guide the selection. This often leads to selecting some emotion words, each presumed to identify a different emotion, even when some of those chosen emotion words have long been shown to be effective markers for the same emotion (Just et al, 2007;Bil-Jaruzelska and Monzer, 2022).…”
Section: Taxonomymentioning
confidence: 99%